The influence of digital literacy and ChatGPT use on the critical thinking ability among library and information science students - Saenal Abidin; Irni Izwah Abu Bakar; Irvan Muliyadi; Ismaya Ismaya; Fendy Fendy; Inawati Inawati (Library and Archive, Universitas Gadjah Mada, 2026)
Introduction. This study, grounded in digital literacy theory, examines how students’ critical thinking abilities are shaped by digital competency and the use of generative AI in educational settings. The main objective is to determine how ChatGPT use and digital literacy together affect the development of critical thinking. The participants are the library and information science students, who are expected to demonstrate strong competencies in information technology and critical information evaluation. Research Methods. This study employed a correlational design involving 106 third-semester students from the 2024 cohort. Responses were obtained using a 1–5 Likert-scale questionnaire. Data Analysis. The data analysisinvolved multiple linear regression, Sobel mediation testing, and bootstrapping. Tests for validity, reliability, and classical assumptions were conducted, and heteroscedasticity was addressed using robust standard errors (HC3). Results. The results highlight that digital literacy and ChatGPT use collectively accounted for 62.2% of the variance in critical thinking skills. ChatGPT use was the strongest predictor (β = 0.535) and partially mediated the relationship between digital literacy and critical thinking (indirect effect = 0.342; 95% CI = 0.192–0.455). Conclusion. The study emphasized the importance of integrating digital literacy and ethical AI to enhance students’ critical thinking skills.